1984
DOI: 10.2172/6855591
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic emission monitoring of hot functional testing: Watts Bar Unit 1 Nuclear Reactor

Abstract: Acoustic emission CAE) moni toring of selected pressure bo u ndary areas at TVA ' s Watts Bar , Unit 1 Nuclear Power Plant d u ring hot functiona l preservice testing is descr i bed in t his report.The report deal s wi th background, methodology , and resu l ts .The work discussed here is a major milestone in a program s u p p orted by NRC to develop an d demonstrate application of AE moni toring for continuous surveil l ance of r eactor p ressure boundaries to detect and evaluate growing flaws.The subject wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
2

Year Published

1988
1988
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 0 publications
0
5
0
2
Order By: Relevance
“…The specimen was designed such that the system operating temperature would impose thermal loads and cause crack growth. The test results showed that coolant flow noise can be filtered out, and that the acoustic emission signals from a fracture specimen can be detected under operating conditions [Hutton et al 1984]. Acoustic emission was also used to monitor possible crack growth during the 1987 hydrotest of the High Flux Isotope Reactor located at the Oak Ridge National Laboratory; no evidence of crack growth was detected [Hutton 1989].…”
Section: Acoustic Emission Monitoringmentioning
confidence: 99%
“…The specimen was designed such that the system operating temperature would impose thermal loads and cause crack growth. The test results showed that coolant flow noise can be filtered out, and that the acoustic emission signals from a fracture specimen can be detected under operating conditions [Hutton et al 1984]. Acoustic emission was also used to monitor possible crack growth during the 1987 hydrotest of the High Flux Isotope Reactor located at the Oak Ridge National Laboratory; no evidence of crack growth was detected [Hutton 1989].…”
Section: Acoustic Emission Monitoringmentioning
confidence: 99%
“…AE relies on the (usually long-range) detection of stress waves that emanate from damage sites, either intrinsically due to the growth process of the damage or as a result of an external applied load to the 4.4 component. AE is well suited for online monitoring of passive components in nuclear power plants, and has been applied for crack growth detection (Harris and Dunegan 1974;Hutton et al 1984;Hutton 1993;Hutton et al 1993;Ai et al 2010;Meyer et al 2011b), leak detection (IAEA 2008b), and loose part monitoring (IAEA 2008b). GW also relies on the interaction of long-range stress waves with damage in the component (Rose 1999;Meyer et al 2012b).…”
Section: Data Collection -Nde For Passives Variable Sensing For Activesmentioning
confidence: 99%
“…A number of studies on the use of AE for monitoring nuclear components have been performed, and applications include crack growth monitoring, leak detection, and loose part detection and monitoring (Harris and Dunegan 1974;Hutton et al 1984;Hutton 1993;Hutton et al 1993;IAEA 2008b;Ai et al 2010;Meyer et al 2011b). AE was also deployed for a limited field trial to monitor the growth of cracks in two RPV nozzles at Limerick Generating Station Unit 1 (BWR) reactor and the Watts Bar Unit 1 (PWR) reactor (Hutton et al 1991;Hutton et al 1993).…”
Section: Metalsmentioning
confidence: 99%
“…На третьому етапі АЕ-моніто-ринг проводили на діючому реакторі Watts Bar Unit 1 як під час гідростатичних передексплу-атаційних випробувань, так і під час пуску ре-актора та його роботи. Задля кількісної оцінки параметрів АЕ-сигналів та ефективної локації джерел АЕ здійснювали окрему процедуру калі-брування каналів АЕ-системи із використанням АЕ-імітаторів [26].…”
unclassified
“…До пе-реліку завдань, поставлених для досліджень, на-лежить розпізнавання сигналів АЕ, які є характер-ними тільки для росту тріщини та встановлення кореляцій між параметрами сигналів АЕ та роз-витком руйнування [15][16][17][18][19][20][21][22][23][24][25][26][27].…”
unclassified